2014
DOI: 10.1186/1471-2407-14-659
|View full text |Cite
|
Sign up to set email alerts
|

The saga of the many studies wrongly associating mitochondrial DNA with breast cancer

Abstract: BackgroundA large body of genetic research has focused on the potential role that mitochondrial DNA (mtDNA) variants might play on the predisposition to common and complex (multi-factorial) diseases. It has been argued however that many of these studies could be inconclusive due to artifacts related to genotyping errors or inadequate design.MethodsAnalyses of the data published in case–control breast cancer association studies have been performed using a phylogenetic-based approach. Variation observed in these… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
30
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(34 citation statements)
references
References 44 publications
4
30
0
Order By: Relevance
“…[23][24][25]). In this study, we have attempted to show whether the mtDNA haplogroup of a person confers a genetic susceptibility to drug addiction and HIV-1 infection in Chinese individuals from Southwest China.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…[23][24][25]). In this study, we have attempted to show whether the mtDNA haplogroup of a person confers a genetic susceptibility to drug addiction and HIV-1 infection in Chinese individuals from Southwest China.…”
Section: Discussionmentioning
confidence: 97%
“…However, a number of these studies had a high incidence of false positive associations due to various errors, and rigorous methodological and statistical standards in mtDNA genetic association studies should be performed to avoid any false positive associations between mtDNA variants and neurological diseases or between mtDNA variants and cancer (cf. [23][24][25]). We hypothesize that the inherited mtDNA haplogroup may affect the risk of drug addiction and the subsequent risk of acquiring HIV-1 infection.…”
Section: Introductionmentioning
confidence: 97%
“…In a study performed by Mosquera-Miguel et al also no association was found for this variation in a Spanish population [121]. Recently, Salas et al reanalyzed all studies and no correlation could be found regarding the m.10398A>G SNP [122].…”
Section: Germline Mtdna Mutations Associated With Cancermentioning
confidence: 88%
“…Due to in‐proper use of statistical methods and some other questionable issues in previous published works, a reassessment of mtDNA haplogroups in the occurrence of breast cancer was made recently . In our previous study, we found that haplogroup D5, which is a sub‐haplogroup of the M macro‐haplogroup, had a significantly higher frequency in patients with breast cancer compared to that found in control subjects ( p = 0.03) .…”
Section: Discussionmentioning
confidence: 92%
“…In the past decade, multiple mtDNA haplogroups were identified and associated with breast cancer in different populations . Previously, haplogroup D5 was found to be a risk factor for multiple cancer types including breast cancer, although other studies found that D5 did not significantly contribute to predisposition to prostate cancer or breast cancer . To address these contradictory findings, and to better understand whether haplogroup D5 has a role in cancer occurrence, and in particular breast cancer, we aimed to elucidate the role of mtDNA haplogroup D5 in breast cancer at both the genetic and molecular levels using a case‐control study with a large cohort of women with breast cancer from Southern China and functional analyses using trans‐mitochondrial approaches.…”
mentioning
confidence: 99%